AVALIAÇÃO DE RISCO DE ULCERAÇÃO EM USUÁRIOS DIABÉTICOS - Nascimento, Renata Lira do; França, Suzana Kelly Coutinho; Andrade, Cinthia Rafaela Amaro Gonçalves; Alencar, Mônica Valença de; Costa, Laís de Miranda Crispim (Gep News, 2019)
Trabalho Premiado em PRIMEIRO LUGAR - Modalidade Comunicação Oral